AN EVALUATION OF COMMUNICATION STRATEGIES USED IN POLIO IMMUNIZATION CAMPAIGNS IN KADUNA AND SOKOTO STATES, NIGERIA (2016)
One of the fundamental factors that determine the success or failure of a behavioural change campaign is the nature of communication strategies adopted by the change agent. Nigeria has been declared a polio free nation, but scholarly attention has not been given to the role played by communication strategies in the success of polio immunisation and eradication projects in Northern Nigeria. This study, therefore, investigated the communication strategies used in polio immunisation campaigns in Kaduna and Sokoto states, the extent of participation in the design and implementation of these strategies, the influence of demographic, socio-cultural variables and knowledge on acceptance and use of polio vaccine. Health Belief Model, Multi-Step Flow and Knowledge Gap theories were adopted. Five key informant interviews were conducted with one each of parent, opinion/religious leader, UNICEF/WHO official, health reporter, and Federal Ministry of Health worker, each of whom was purposively selected. A semi-structured questionnaire was administered on 200 parents/guardians purposively selected from Kwarbai, Sabon Fegi, in Kaduna State; Dange Shuni and Sokoto Municipal in Sokoto State. Four focus group discussion sessions comprising 10 participants from each study area were conducted with parents who have children aged between one and five years. Quantitative data were analysed using descriptive and chi-square statistics at p< 0.05, while qualitative data were content analysed. Strategies used in the two states were advocacy, social mobilisation and programme communication. Their manifestations were: Advocacy: (Kaduna-79.8%, Sokoto-70.0%) and Social Mobilization: (Kaduna-69.2%, Sokoto-84.7%). The programme communication in Kaduna (74.7%) and Sokoto (84.7%) showed that the responses did not conform on the issue of acceptance of a singular communication strategy (x2=314.7). The need to adopt multiple communication strategies in both states was reiterated. The implementation of the contents of polio campaign strategies was low (x2=15.9). Adoption of multiple communication strategies was more effective in both states (x2=314.7). Demographic factors influenced their acceptance and use of polio immunisation as there was conformity in response across the two states (x2=0.1). Socio-cultural variables influenced acceptance and use of polio vaccine (x2=0.1). Respondents’ knowledge and awareness of polio immunisation influenced them to accept and use polio vaccine. Adoption of different communication strategies led to increased acceptance and use of polio immunization among parents/guardians in Kaduna and Sokoto States. Multi-dimensional communication strategies should be used in order to achieve maximum success in immunisation campaign to eradicate polio in Nigeria.